Costly, confusing, polarizing, and suspect: public perceptions of plant- based eating from a thematic analysis of social media comments - Eckert, Katherine F.; Douglas, Sabrina; Zhang, Flora; Brauer, Paula; Duncan, Alison M.; Haines, Jess (Frontiers in Sustainable Food Systems, 2024)
Introduction: A key approach to fostering more sustainable food systems involves shifting dietary patterns towards increased plant-based eating. However, plant-based eating remains low among Canadians. The objective of this research was therefore to explore public perceptions of plant-based eating in a Canadian context. Methods: A qualitative design was used to analyze social media comments posted on Canadian news source Facebook articles between January 16th, 2019 – July 16th, 2020. Investigating perceptions of plant-based eating on social media may capture a broader sample of the population than can be captured using other qualitative methods. Template analysis, a type of codebook thematic analysis, was used to generate themes and subthemes using NVivo software. Results: Nine articles were selected for inclusion and a total of n=4,918 comments were collected. Five themes and nineteen subthemes related to plant-based eating were generated and presented with quotations. Themes included: (1) The ethics of food; (2) The affordability and accessibility of food; (3) Distrust of food system stakeholders; (4) Beliefs related to dietary behavior, health, and the environment; and (5) Sensory aspects of plant-based proteins. Discussion: Findings suggest that addressing food affordability and accessibility, increasing public food literacy, using non-judgmental approaches, and increasing food system transparency and communication may be strategies to foster plant-based eating. Results of this study provide insight for the development of more effective public health messaging about plant-based eating and help inform future research and interventions to address barriers related to plant-based eating and promote consumption.